Politik Etnisitas Dalam Upaya Pemekaran Provinsi Kotawaringin - Ricky Zulfauzan; Kris Nugroho; Dwi Windyatuti (Jurnal Sosial Humaniora, 2019)
This study aims to provide a descriptive analysis of ethnicity politics from theperspective of Glazer and Moynihan "Beyond The Melting Pot" to expandKotawaringin Province. The research method used is qualitative with a casestudy approach. The research data were obtained from observations,document searches and in-deep interviews. The results found that the desireto separate from Central Kalimantan Province made the five prospectiveregencies of Kotawaringin Province form a Melting Pot. "Melting Pot," whichis meant here, is to be "Orang Kotawaringin." The Kotawaringin communityis very heterogeneous, originating from not only one ethnicity but being ableto unite for a common goal.In contrast to Glazer and Moynihan's "Being America," which illustrates thepattern of ethnic interaction in New York City is eternal. In Kotawaringin, thisethnic identity is only temporary and impermanent. The collective identity ofbeing an Orang Kotawaringin is built according to an instrumentalistperspective, namely: ethnicity is seen not only as a given value or as a resultof a social construction but rather as used to obtain benefits, including federalbenefits.